AMOXICILLIN AND TETRACYCLINE ACTIVITY AGAINST STAPHYLOCOCCUS AUREUS AND PROTEUS MIRABILIS - Ayub, Sonia; Fatima, Bilqees; Baqir, Syed; Naqvi, Shyum; Sheikh, Dilnawaz; Ali, Syed Muzaffar; Khaliq, Sheikh Abdul (International Journal of Current Pharmaceutical Research, 2015)
Objective: Present investigation was undertaken to evaluate the susceptibility and resistance pattern of clinical isolates causing different types of infections and to compare the efficacy of antibiotics namely amoxicillin and tetracycline. Methods: The in-vitro antibacterial activity and resistance patterns of these two well known antibiotics were studied and compared by using the disk diffusion method. For this, one hundred and thirty four clinical isolates comprising of, Staphylococcus aureus (103) and Proteus mirabilis (31) and information were taken regarding patient age, sex and bacterial organism isolation were collected from different local pathological laboratories and hospitals according to the zones (east Karachi, west Karachi, south Karachi and north Karachi) of Karachi (Pakistan) during the time period of February 2015 to June 2015. Results: Out of the sample analyzed, resistant pattern of one hundred and thirty four (134) clinical isolates of Staphylococcus aureus (103) and Proteus mirabilis (31) were studied by using amoxicillin and tetracycline and the results are among 103 samples of Staphylococcus aureus 4(3.9%) sample showed sensitivity, no clinical isolates showed intermediate response and 99 (96.1%) sample exhibited resistance against amoxicillin while, 84 (81.6%) sample of Staphylococcus aureus were sensitive against tetracycline, 6(5.8%) showed intermediate response and 13(12.6%) were resistant to the tetracycline 30 Âµg while, 2 (6.5%) clinical isolates showed sensitivity towards Proteus mirabilis, 19(61.31%) showed resistance and 10 (32.3%) showed intermediate resistance against amoxicillin. On the other hand, tetracycline showed 3(9.7 %) resistance against Proteus mirabilis, 26(83.9%) showed sensitivity and 2 (6.5%) clinical isolates showed intermediate resistance. Conclusion: overall results of the present study showed that the antibacterial activity of tetracycline is more as compare to amoxicillin. Amoxicillin is not the first choice to treat the infections against Proteus mirabilis and Staphylococcus aureus because they showed resistance 96.1% and 61.3% against Proteus mirabilis as compare to tetracycline is the first choice to treat infection which is caused by Staphylococcus aureus and Proteus mirabilis because they showed 81.6% sensitivity against Staphylococcus aureus and 83.9% sensitive against tetracycline.